Scope and interrelation of horizontal collusion practices within the framework of law on the repression of anti-competitive conduct - Borda Gianella, Waldo (2020)
In this article, the author analyses the scope and interrelationship between the concepts of agreement, decision, recommendation and concerted practice in the light of comparative doctrine and jurisprudence, taking particular account of the case law of the Court of Justice of the European Union. In an introductory way, the scope of some of these concepts, outlined by Peruvian doctrine and jurisprudence, are presented, identifying the inconsistencies between these and the developments at a comparative level. Then we proceed with the formulation of a proposal of interpretation of the scope and interrelationship existing between these four concepts, which gives final pass to the identification of the implications generated with the proposed proposal.The relevance of the points addressed is supported by: (i) the increase in the number of procedures for horizontal collusive practices initiated by the Technical Secretariat of the Commission for the Defense of Free Competition of Indecopi in recent years; (ii) the limited national case law on the interrelationship between cases of horizontal collusive practice and their application in the context of the administrative penalty procedure; and, (iii) the limited development of the national doctrine on the interrelationship between cases of horizontal collusive practice and their implications in practice.